Dental treatment and employment outcomes among social assistance recipients in Ontario, Canada. Issue 10 (October 2016) - Singhal, Sonica; Mamdani, Muhammad; Mitchell, Andrew; Tenenbaum, Howard; Lebovic, Gerald; Quiñonez, Carlos
Highlights: First Canadian study to explore relationship between dental treatment and employment outcomes. At one year, social assistance recipients who received or did not receive dental treatment had similar employment outcomes. Over the one year time period, the change in proportions of leaving assistance was more pronounced for treatment recipients. Dental treatment potentially addresses some deficiencies and level-up disadvantaged in terms of their employment outcomes. This knowledge is important for policy debates for timely dental treatment for the marginalized. Abstract: Background: Policy advocates continue to argue for the expansion of dental care services for people on social assistance in order to meet their health needs and to promote the move from welfare-to-work. However, there is little to no evidence to support the idea that receiving dental care ultimately improves employment outcomes. Methods: A retrospective cohort study was designed using administrative data from five Ontario regions and from the province's social assistance ministry. Employment outcomes among treatment and no-treatment cohorts were assessed at three, six and 12 months from baseline. Multivariable regression modeling was performed. Results: We received data for 8742 people (2742 treatment, 6000 no-treatment). At one year, employment outcomes were not significantly different between the two groups (adjusted odds ratio = 0.93; 95% CI: 0.83–1.03). Post-hoc analysis show that the change in proportion of individuals leaving social assistance for employment over time was significantly higher (p = 0.0014) among those receiving treatment (13–29%; 124% increase) than those not receiving treatment (18–33%; 83% increase). Conclusion: At one year, dental treatment alone does not appear to be significantly associated with leaving assistance for employment in this population. However, this study suggests that people who received dental treatment may have been particularly disadvantaged and dental treatment may help to level them up in terms of employment outcomes over time.